SURFACE MORPHOLOGY ANALYSIS OF CONNECTING ROD AND CRANKSHAFT OF COMPRESSOR UNDER DIFFERENT WORKING CONDITIONS - LIN ShaoJiang; LI Shun; DAI JingXiong; HE GuoGeng (Jixie qiangdu)
In order to explore the influence of different working conditions on the surface morphology of crankshaft and connecting rod of compressor,the roughness meter was used to measure the surface morphology characterization value of connecting and crankshaft based on the compressor reliability test. The results show that the working conditions of the compressor have a great influence on the surface morphology of the crankshaft and connecting rod. With the increase of work time,the Ra value of compressor parts surface increases,but the Rzvalue of connecting rod surface decreases obviously. The start-stop of the compressor also has some influence on the surface morphology of the moving parts. With the increase of start-stop times,the values of Raand Rzof connecting rod surface decrease,while the values of Raand Rzof crankshaft surface increase slightly.Through analysis it can be known that the crankshaft and connecting rod are in normal wear stage after running 672 h and 1 344 h at 43℃ . The connecting rod is still in the initial wear stage and the crankshaft is in the normal wear stage after 125,000 and250,000 start-stop cycles respectively at 25℃ .